The Acute Effects of Small-Sided Games on Hamstring Strength in Young Soccer Players - Italo Sannicandro; Giacomo Cofano; Gaetano Raiola (OVS LLC, 2022)
The study purpose.The Small-side games (SSG) are high intensity drills very popular in soccer training. The knowledge of the acute effects of the exercises that make up the training session is very relevant especially to reduce youth soccer injury risk. This study aim to assessment the acute effects of SSG on hamstring eccentric strength and to know the lower limb strength asymmetries (LLSA) in young soccer players. Materials and methods. The sample is composed of male young soccer players Under 17 (n = 24, 16.6 ± 0.5 years, 168.8 ± 4.6 cm, 58.2 ± 3.5 kg). Before and after SSG (4vs4, 3×4 min, 3min recovery, no goalkeepers) the hamstring eccentric strength and the lower limb eccentric strength asymmetry were evaluated used a specific dynamometer (N3 Easytech, Italy) and relative software. Every young soccer player performed a single repetition of the Nordic hamstring exercise with dynamometer; after about 2 minutes, instead, they performed 5 repetitions of the same exercise, without interruption. For both assessments, were detected the eccentric strength and the LLSA.  Results. The hamstring eccentric strength assessment show substantial and statistically significant differences in the assessment in comparison pre-post values. A significant reduction was observed for eccentric strength peak (p < 0.018 and p < 0.014 for right/left limb), for eccentric average strength (p < 0.017 and p < 0.006 for right/left limb). The eccentric peak strength asymmetry value and the average strength asymmetry value revealed a significant increase (p < 0.0001).  Conclusions. The reduction of strength after SSG requires careful consideration of the exercises order in the training session. The practitioners can plan training sessions and apply SSGs more effectively, with more attention to the effects on hamstrings.